Synthesis of Non-benzidine Reactive Dyes and Their Application on Various Fibres - Patel, R.S.; Patel, P.S.; Patel, K.C.; Patel, S.K. (Asian Journal of Chemistry, 2010)
Various bisazo reactive dyes have been prepared by coupling diazotised 4,4´-diaminodiphenylsulphonamide with various cyanurated coupling components such as H-acid, Peri acid, Bronner's acid, J-acid, Tobias acid, N-methyl-J-acid, Gamma acid, Laurent acid, Chicago acid and T-acid and their dyeing performance as reactive dyes has been assessed on silk, wool and cotton fibres.